Collaborative working in the resettlement of young people leaving custody. Issue 3 (17th June 2020) - Olaitan, Paul; Pitts, John
Abstract : Purpose: This paper aims to endeavour to sketch out a blueprint for effective collaborative working in resettlement. Design/methodology/approach: The paper is based on a review of the relevant research and interviews with professionals concerned with the resettlement of young people from custody in organisations and agencies that were partners in the Beyond Youth Custody programme. Findings: Practitioners working on the youth resettlement pathway between custody and community report collaborative practices to be more beneficial both to the young people involved as well as the practitioners themselves, in the conduct of their efforts. Originality/value: To the best of the authors' knowledge, the originality of this paper consists in its investigation of resettlement practice by consulting those actually engaged in the resettlement process.